Market Access, Supplier Access, and Africa's Manufactured Exports : An Analysis of the Role of Geography and Institutions - Elbadawi, Ibrahim; Mengistae, Taye; Zeufack, Albert (World Bank, Washington, DC, 2012)
In a large cross-country sample of manufacturing establishments drawn from 188 cities, average exports per establishment are smaller for African firms than for businesses in other regions. The authors show that this is mainly because, on average, African firms face more adverse economic geography and operate in poorer institutional settings. Once they control for the quality of institutions and economic geography, what in effect is a negative African dummy disappears from the firm level exports equation they estimate. One part of the effect of geography operates through Africa's lower "foreign market access:" African firms are located further away from wealthier or denser potential export markets. A second occurs through the region's lower "supplier access:" African firms face steeper input prices, partly because of their physical distance from cheaper foreign suppliers, and partly because domestic substitutes for importable inputs are more expensive. Africa's poorer institutions reduce its manufactured exports directly, as well as indirectly, by lowering foreign market access and supplier access. Both geography and institutions influence average firm level exports significantly more through their effect on the number of exporters than through their impact on how much each exporter sells in foreign markets.